EDUKASI BERMAIN SEBAGAI STIMULASI TUMBUH KEMBANG ANAK - Nesi Nesi; Cicilia Febriani Hayuningrum; Dela Fariha Fuadi; Andrew Wijaya S (PENA ABDIMAS : Jurnal Pengabdian Masyarakat, 2022)
Games is one of the most effective ways to stimulate children's development. Every stage of child's age has a different type of game that is suitable for their growth and development. Since COVID-19 pandemic, there was some limitation of playing area that could affect development of some stage of child’s age. Parent felt confusion due to the long duration of the COVID-19 pandemic began to watch ideas in providing stimulation to children. This community service is provide to educate about the objectives and types of games that are in accordance with the stages of child development. Community service is carried out using online meeting media. Participants in this community service were parents and prospective parents (55 people) and physiotherapy students (9 people). The participants were given a pretest and posttest to see an increase in understanding before and after get education. The results of the study showed that the participants' understanding had increased (M: 36.56, SD: 16.54). With this community service, it is hoped that parents can facilitate their children by providing appropriate games in order to optimize their child growth. Keywords:  play, stimulation, development.